2020
DOI: 10.1016/j.virusres.2020.198103
|View full text |Cite
|
Sign up to set email alerts
|

Immunological co-ordination between gut and lungs in SARS-CoV-2 infection

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has evolved into a major pandemic called coronavirus disease 2019 (COVID-19) that has created unprecedented global health emergencies, and emerged as a serious threat due to its strong ability for human-to-human transmission. The reports indicate the ability of SARS-CoV-2 to affect almost any organ due to the presence of a receptor known as angiotensin converting enzyme 2 (ACE2) across the body. ACE2 receptor is majorly expressed in the brush border … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 80 publications
0
95
0
5
Order By: Relevance
“…The affinity of SARS-CoV-2 to the respiratory epithelium and gastrointestinal epithelium is because of the receptor angiotensin-converting enzyme-2[ACE-2] in the brush border of gut enterocytes and lungs alveolar epithelial type II cells ( Hoffmann et al, 2020 ). The presence of viral RNA of SARS-CoV-2 in faecal samples of COVID-19 patients ( Ahlawat et al, 2020 ) confirm their gut inhabitation. The co-infection in the gut impairs the physiology of the gut and eliminates “Good “bacteria making an imbalance between good and bad bacteria (dysbiosis) ( Trottein and Sokol, 2020 , Lin et al, 2020 ).…”
Section: Probiotic Role In Sars-cov-2 Infectionmentioning
confidence: 80%
“…The affinity of SARS-CoV-2 to the respiratory epithelium and gastrointestinal epithelium is because of the receptor angiotensin-converting enzyme-2[ACE-2] in the brush border of gut enterocytes and lungs alveolar epithelial type II cells ( Hoffmann et al, 2020 ). The presence of viral RNA of SARS-CoV-2 in faecal samples of COVID-19 patients ( Ahlawat et al, 2020 ) confirm their gut inhabitation. The co-infection in the gut impairs the physiology of the gut and eliminates “Good “bacteria making an imbalance between good and bad bacteria (dysbiosis) ( Trottein and Sokol, 2020 , Lin et al, 2020 ).…”
Section: Probiotic Role In Sars-cov-2 Infectionmentioning
confidence: 80%
“…After SARS-CoV-2 invaded the lung, host immune system was activated and inflammatory cytokines were released. Pulmonary permeability was increased with the release of inflammatory cytokines, which further led to viral invasion of the gut through the gut-lung axis, and vice versa ( Ahlawat et al, 2020 ). In these processes, the intestinal flora acted as a “bridge”.…”
Section: Coronaviruses and Gastrointestinal Lesionsmentioning
confidence: 99%
“…In addition, it has been demonstrated that ACE2 is also abundantly expressed in gastrointestinal epithelial cells ( 56 , 57 ). Therefore, host cell internalization of SARS-CoV-2 may be identified in the gastrointestinal tract, and can lead to active infection and replication ( 13 ).…”
Section: Two-stage Interaction With Receptors On Host Cellsmentioning
confidence: 99%